Evaluation of a copper(I)-Biquinoline complex modified electrode for electrochemical detection of nitrite in water - (:unkn) unknown (ELSEVIER SCI LTD, 2026)
Glassy carbon electrodes were modified with a small amount of Nafion and a novel copper (I)-biquinoline coordination compound. Their electrochemical properties were evaluated for the detection and quantification of nitrite in aqueous media. The surface of the resulting stable and reproducible electrodes was characterized by Raman spectroscopy and atomic force spectroscopy (AFM). Electrochemical measurements in Britton-Robinson buffer revealed an increased current response and a decrease in onset potential for nitrite reduction compared with bare glassy carbon electrode. The modified electrode exhibited a linear response (R2 = 0.998) a detection limit of ca 0.04 mu M and recovery values of 88.9 +/- 0.05 % in model water, 43.2 +/- 0.04 % in drinking water and 23.9 +/- 0.31 % in well water. Chronoamperometric measurements at -0.86 V (vs Ag/AgCl) demonstrated that no other ions interfered with the electrochemical response of Cu(I)-biquinoline modified electrodes.